Electricity generation potential of sewage sludge in sediment microbial fuel cell using Ti-TiO2 electrode - Taskan, Banu; Taskan, Ergin; Hasar, Halil (Wiley, 2020)
The aim of this study is to increase the electricity generation capacity of sediment microbial fuel cell (SMFC) using sewage sludge as a substrate source in anode media via an attractive electrode material. For this purpose, several electrochemical and molecular techniques have been employed to evaluate the performance of SMFC. The max power density and charge transfer resistance of SMFC running on sewage sludge were 187 mW/m(2) and 84.7 omega, respectively. The polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) analysis indicated that bacteria in anode biofilm belonged to the Clostridia, d-proteobacteria, g-proteobacteria, and b-proteobacteria. Scanning electron microscopy and fluorescence in situ hybridization observations demonstrated that a viable biofilm was formed on the anode surface and the abundance of bacteria was significantly higher than archaea. Consequently, this study showed that sewage sludge could be used as a substrate in the anode media of SMFC for producing high power density.
Keywords: fuel cell; microbial dynamics; power generation; sediments; sewage sludge